Islamizing Intimacies Youth, Sexuality, and Gender in Contemporary Indonesia - Smith-Hefner, Nancy J. (University of Hawai'i Press, 2019)
One of the great transformations presently sweeping the Muslim world involves not just political and economic change but the reshaping of young Muslims' styles of romance, courtship, and marriage. Nancy J. Smith-Hefner takes up the personal lives and sexual attitudes of educated Muslim Javanese youth in the city of Yogyakarta to explore the dramatic social and ethical changes taking place in Indonesian society. Drawing on more than 250 interviews over a fifteen-year period, her vivid, well-crafted ethnography is full of insights into the real-life struggles of young Muslims and framed by a deep understanding of Indonesia's wider debates on gender and youth culture. The changes among Muslim youth reflect an ongoing if at times unsteady attempt to balance varied ideals, ethical concerns, and aspirations. On the one hand, growing numbers of young people show a deep and pervasive desire for a more active role in their Islamic faith. On the other, even as they seek a more self-conscious and scripture-based profession of faith, many educated youth aspire to personal relationships similar to those seen among youth elsewhere-a greater measure of informality, openness, and intimacy than was typical for their parents' and grandparents' generations. Young women in particular seek freedom for self-expression, employment, and social fulfillment outside of the home. Smith-Hefner pays particular attention to their shifting roles and perspectives because it is young women who have been most dramatically affected by the upheavals transforming this Muslim-majority country. Although deeply personal, the changing aspirations of young Muslims have immense implications for social and public life throughout Indonesia. The fruit of a longitudinal study begun shortly after the fall of the authoritarian New Order government and the return to democracy in 1998-1999, the book reflects Smith-Hefner's nearly forty years of anthropological engagement with the island of Java and her continuing exploration into what it means to be both "modern" and Muslim. The culture of the new Muslim youth, the author shows, through all its nuances and variations, reflects the inexorable abandonment of traditions and practices deemed incompatible with authentic Islam and an ongoing and profound Islamization of intimacies.